The Influence Of Learning Model Application of Discovery To The Results of The Study of Biology - Harahap, Arman; Rafika, Mulya; Harahap, Paramadi (International Journal of Educational Research & Social Sciences, 2020)
This research was conducted in the upper secondary school Panai Middle years learning 2018/2019. This study aims to determine the influence of learning model application of Discovery to student learning outcomes on the material the human excretory system in class XI Science. This type of research is quasi-experimental. Population, all students of class XI Science high school Panai Tenga amounted to 32 people. The sampling technique is total sampling, where the entire population in the study sample. The instruments used are test, observation sheet and questionnaire. Data were analyzed using descriptive statistics, test prerequisites and the test of hypothesis with the help of SPSS software version 22.From the results of the hypothesis test, t-test paired samples (Paired Sample t-test), obtained the value of tcount of 5, 422 and ttable with α = 0.05, df = 15, the obtained values ttable amounted to 2,131. The value of tcount > ttable or 5,422 > 2,131 can be concluded that H0 is rejected and Ha accepted. This means that there is significant influence of learning model application of Discovery to student learning outcomes in class XI Science high school Panai Middle years learning 2018/2019.